STUDI EVALUASI PENGENDALIAN BIAYA (COST CONTROL) DAN JADWAL PELAKSANAAN (SCHEDULING) PADA PROYEK PEMBANGUNAN GEDUNG RAWAT JALAN DAN BASSEMENT RSUD MAJALENGKA MENGGUNAKAN METODE EARNED VALUE DAN SOFTWARE MS. PROJECT : Indonesia - Arief Rijaluddin (Universitas Majalengka, 2021)
Planning and controlling costs and time is part of the overall construction project management. In addition to the assessment in terms of quality, the achievement of a project can also be assessed in terms of cost and time. The costs that have been incurred and the time spent in completing a job must be measured continuously for deviations from the plan. The presence of significant cost and time deviations indicates poor project management. With the existence of project performance indicators in terms of cost and time this allows preventive actions so that project implementation goes according to plan. The concept of